1998
DOI: 10.1126/science.279.5348.214
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Boreal Forest Carbon Balance to Soil Thaw

Abstract: We used eddy covariance; gas-exchange chambers; radiocarbon analysis; wood, moss, and soil inventories; and laboratory incubations to measure the carbon balance of a 120-year-old black spruce forest in Manitoba, Canada. The site lost 0.3 ± 0.5 metric ton of carbon per hectare per year (ton C ha −1 year −1 ) from 1994 to 1997, with a gain of 0.6 ± 0.2 ton C ha −1 year −1 in moss and wood offset by a loss of 0.8 ± 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
513
8
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 718 publications
(547 citation statements)
references
References 19 publications
18
513
8
8
Order By: Relevance
“…It is wellknown that if moss cover thickness incieases, thermoisolation of soil also increases, summer soil thawing decreases, and tree growth is suppressed by nearer permafrost. During long warm periods with higher annual and seasonal (June-September) temperatures, owing to deeper soil thawing the moss destruction and organic decomposition in soil may prevail over moss increment on surface and moss thickness decreases [Goulden et al, 1998]. This leads to better thermal conditions tbr roots of trees and finally to the increase of the growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…It is wellknown that if moss cover thickness incieases, thermoisolation of soil also increases, summer soil thawing decreases, and tree growth is suppressed by nearer permafrost. During long warm periods with higher annual and seasonal (June-September) temperatures, owing to deeper soil thawing the moss destruction and organic decomposition in soil may prevail over moss increment on surface and moss thickness decreases [Goulden et al, 1998]. This leads to better thermal conditions tbr roots of trees and finally to the increase of the growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Many modeling and fieldbased studies have also reported a high interannual variability of ecosystem CO 2 sources and sinks (Woofsy et al, 1993;Goulden et al, 1996;Chen et al, 2002). Researchers conducting fieldbased eddy covariance studies have noted that in some instances a warm winter can switch a boreal forest from becoming a carbon sink to a source due to an increase in ecosystem respiration (Lindroth et al, 1998;Goulden et al, 1998). This has been attributed to climatic variability and the correlation between temperature and ecosystem respiration .…”
Section: Variability In Nepmentioning
confidence: 99%
“…If these soils are warmed, decomposition and emissions of CO 2 and CH 4 will proceed rapidly, leading to a large positive feedback with climate change. Indeed, year-to-year differences in decomposition of old SOM in some boreal forest soils can determine the status of entire forest stands as net sources or sinks of C (Goulden et al 1998). Because gross C fluxes at high latitudes are small compared to those in the tropics, it is unlikely that even large interannual variability in those fluxes could be as important in affecting the short term (annual) C balance of the atmosphere.…”
Section: Climate Changementioning
confidence: 99%